Resolusi Konflik Tapal Batas Kabupaten Rokan Hulu Dan Kabupaten Kampar, Propinsi Riau - Surya Ningsih; Silsila Asri (LPPM Universitas PGRI Sumatera Barat, 2016)
Conflict between Rokan Hulu District and Kampar District in Riau ProvinceÂ is conflict about the seizing territory of five villages on the border in both districts. Litigation process which was persued by the central government inresolving the conflict in the border of both districts did not solve that problem. Both districts do not accept the decision that has been arranged by the central government. It was proved by the allocation of village budget for the five villages from the both districts. This also lead to social tension and conflict in the community of five villages which then make the conflict more widespread. This study used a qualitative method and aim to describe the conflict resolution in the determining the boundary between District of Rokan Hulu and District of Kampar.Â Konflik antara Kabupaten Rokan Hulu dengan Kabupaten Kampar di Provinsi Riau merupakan perebutan lima desa yang ada diperbatasan kedua Kabupaten. Jalur Litigasi/peradilan yang ditempuh oleh pemerintah pusat dalam menyelesaikan konflik di tapal batas kedua kabupaten tidak menyelesaikan persoalan. Kedua kabupaten tidak menerima keputusan yang telah ditetapkan oleh pemerintah pusat dengan masih diberikannya Alokasi Dana Desa di lima desa oleh masing-masing kabupaten. Hal ini kemudian memicu ketegangan dan konflik sosial di masyarakat lima desa yang membuat konflik semakin meluas. Penelitian ini menggunakan metode kualitatif dan bertujuan untuk memaparkan resolusi konflik dalam penentuan tapal batas di Kabupaten Rokan Hulu dan Kabupaten Kampar.